Characterisation of Culex quinquefasciatus (Diptera: Culicidae) larval habitats at ground level and temporal fluctuations of larval abundance in Córdoba, Argentina - Grech, Marta Gladys (2013)
Fil: Grech, Marta Gladys. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones Biológicas y Tecnológicas, Argentina.